Immunity due to COVID-19 vaccination and its correlation with lung involvement severity as an indicator of disease severity - Razieh Mousapour; Mostafa Assarroudi; Yaser Khanchemehr; Masoomeh Mehrbarjou; Golmis Abdolmohammadi; Farshad Gharebakhshi; Erfan Ghanbarzadeh; Hussein Soleimantabar (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is a worldwide challenge; regarding the lack of an effective and efficient drug. It seems that the vaccine is the only modality to save the world from this pandemic. Objectives: This study was conducted to assess the effect of vaccination on preventing pulmonary involvement and the disease severity of COVID-19 patients. Patients and Methods: This descriptive-analytical study was conducted on 247 people with coronavirus disease 2019 infection. Demographic characteristics and vaccination status information were collected. Patients' lung computed tomography scan findings were scored based on the pulmonary involvement percentage, and then according to this score, they were graded into severe, moderate, mild, and without lung involvement. The association between pulmonary involvement and vaccination status were evaluated by Fisher's exact test and logistic regression. Results: Most participants were male, with a mean age of 53.74 ± 10.96 years. Most people (42.9%) were partial-vaccinated. Lungs in 53.3% were with lung involvement and in 46.6% were without. The correlation between pulmonary involvement and vaccination was significant (P<0.001). Conclusion: Vaccination is an effective and efficient method in preventing coronavirus disease 2019 severity.